1981
DOI: 10.1146/annurev.pa.21.040181.002455
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphorus Ester-Induced Delayed Neurotoxicity

Abstract: In certain animals, including humans, exposure to some organophosphorus esters causes delayed neurotoxicity (OPIDN). The clinical condition becomes manifest after a delay period, first as ataxia, followed by paralysis. Lesions are characterized by degeneration of axons with subsequent secondary degeneration of myelin in the peripheral and central nervous systems. Recovery is only likely in mild cases, whereas more severe cases show symptoms of an upper motor neuron lesion in the lower limbs. The risk of use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0
3

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 395 publications
(104 citation statements)
references
References 97 publications
(156 reference statements)
4
95
0
3
Order By: Relevance
“…Similar result was obtained by Buhalla et al (2007) who found a significant increase in LPO level in brain tissue after Li treatment. Peroxidation of polyunsaturated fatty acids leads to degradation of phospholipids and cellular deterioration (Abou-Donia, 1981). The present result showed that Zn, VE and their interaction countered the LPO produced by Li.…”
Section: Discussionmentioning
confidence: 47%
“…Similar result was obtained by Buhalla et al (2007) who found a significant increase in LPO level in brain tissue after Li treatment. Peroxidation of polyunsaturated fatty acids leads to degradation of phospholipids and cellular deterioration (Abou-Donia, 1981). The present result showed that Zn, VE and their interaction countered the LPO produced by Li.…”
Section: Discussionmentioning
confidence: 47%
“…Pathogenesis is independent of inhibition of acetylcholinesterase (AChE) and can be induced by OP compounds with low acute toxicity (Johnson, 1982;Makhaeva et al, 1987). Although OPIDN has occurred in epidemic proportions throughout the world, accidental episodes are currently rare (Abou-Donia, 1981;Richardson, 1998). Nevertheless, the high human susceptibility to OPIDN (Cole et al, 1998;Lotti, 1987), its insidious onset, and the usually permanent debilitating effects suggest the possibility of neuropathic OP compounds being used as agents for chemical terrorism.…”
Section: And Between Brain and Blood (R = 997) The Results Suggest mentioning
confidence: 99%
“…This possibility points to a common metabolic basis for many distal axonopathies, ie, that neurotoxic compounds deplete energy supplies in the axon by inhibiting nerve fiber enzymes required for the maintenance of energy synthesis and lead to a local blockade of energy-dependent axonal transport (68, tory step, ageing, must take place, leaving a negatively charged phosphorus group attached to the esterase, which is itself tightly bound to membranous material in the nervous system. Studies on the relationship between the chemical structure of organophosphorous esters and their neurotoxic potencies suggest that two hydrophobic areas may be present in the vicinity of the active site of the neurotoxic protein (1). Abou-Donia (1) postulated that delayed neurotoxic organophosphorus esters phosphorylate the active center of neurotoxic target proteins in the axon.…”
Section: Axonal Transport and Distal Axonopathymentioning
confidence: 99%